Empowering and disempowering climate generated by coaches is associated with negative coping control and attentional control in football players: The mediating role of self-confidence and competitive anxiety - Domínguez González, J. A.; Sánchez García, C.; Morales Sánchez, V.; Hernández Mendo, A.; Reigal Garrido, R. E. (International Journal of Sports Science & Coaching, 2024)
The relationship between motivational climate and psychological sporting abilities could be influenced by levels of competitive anxiety and self-confidence. The purpose of this research was to explore the relationships between empowering and disempowering motivational climates with negative coping control and attentional control, analyzing whether there was an effect of self-confidence and competitive anxiety on these relationships. A total of 328 male adolescents, aged between 14 and 18 years (M = 15.85; SD = 1.44), participated in this research. To collect the information, the Empowering and Disempowering Motivational Climate Questionnaire (EDMCQ-C), the Inventario Psicológico de Ejecución Deportiva (IPED), and the Revised Competitive State Anxiety Inventory-2 (CSAI-2R) were used. The structural equation model revealed positive and statistically significant associations between empowering motivational climate and self-confidence, between disempowering climate and competitive anxiety, as well as between self-confidence and psychological sporting abilities (negative coping control and attentional control). On the other hand, the analyses highlighted negative relationships between competitive anxiety and negative coping control, as well as attentional control. Furthermore, the model revealed indirect associations between empowering climate and negative coping control, and attentional control through self-confidence, as well as between disempowering climate and negative coping control, and attentional control through competitive anxiety. This information could be valuable for professionals in the field of sports, including coaches, psychologists, athletes, managers, or even individuals close to the athletes such as family members or mentors.